2003
DOI: 10.1038/sj.ejhg.5200913
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress in the 5-year period after predictive testing for Huntington's disease

Abstract: The paper reports on a 5-year longitudinal study on psychological distress after predictive testing for Huntington's disease (HD) and on correlates of post-test distress. Psychometric tests and questionnaires were used. The tested persons were invited to participate in the follow-up study; the uptake rate was 75% (24 carriers, 33 non-carriers). Three time points were included: baseline, 1 year and 5 years posttest. Five years after the test, mean distress scores of both carriers and non-carriers were within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
105
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(111 citation statements)
references
References 21 publications
4
105
1
1
Order By: Relevance
“…2,13 The few midand long-term studies available suggest that, in general, there is an absence of negative impact after some years, 11,16,19 specifically in relation to anxiety levels. The study by Decruyenaere et al 15 indicates a decrease in the score for anxiety in the long run. It is thus important to study the mid (4 years) and long-term (7 and 10 years) psychological impact of PST in HD with inclusion of the other two neurodegenerative diseases, MJD and FAP.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…2,13 The few midand long-term studies available suggest that, in general, there is an absence of negative impact after some years, 11,16,19 specifically in relation to anxiety levels. The study by Decruyenaere et al 15 indicates a decrease in the score for anxiety in the long run. It is thus important to study the mid (4 years) and long-term (7 and 10 years) psychological impact of PST in HD with inclusion of the other two neurodegenerative diseases, MJD and FAP.…”
Section: Introductionmentioning
confidence: 92%
“…[7][8][9][10]13,14 Although most report on short-term results of PST, some literature already presents long-term psychosocial impacts of HD predictive testing. 3,11,[14][15][16][17][18][19] Two very specific Portuguese diseases, MJD and FAP, also follow a severe neurodegenerative pathway and remain until now without an effective treatment or cure. For MJD, it is important to highlight the frequency of cerebellar ataxia, progressive external ophthalmoplegia, and pyramidal signs.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 There is substantial evidence that a key concern for adults undergoing predictive testing is the potential impact on their loved ones. 6,7,26 Previous studies of young females with a BrCa mutation have identified concerns about their future health on their children's well-being. 15,16 In this study, it was striking that most participants, including the youngest FCM testees, had anticipated how their family members might react to their test result and sought ways to avoid causing them distress.…”
Section: Process Of Adjustingmentioning
confidence: 99%
“…4 The desire to ensure that testing programmes do not cause more harm than good, has led to a considerable body of research on the psychosocial impact of predictive testing in adults, particularly for hereditary breast and ovarian cancer (HBOC) and Huntington's disease (HD). While most studies and reviews report an overall adjustment in the first couple of years post predictive testing, [5][6][7][8] distress levels may start to rise again later, presumably as the time approaches to possible disease onset. 9 Further, individuals may experience difficulties in specific areas of their lives such as family communication 10,11 and discrimination at home and in the work place or with insurance.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, the majority of studies suggest that people are satisfied with their decision to be tested and cope well when adequately prepared to receive an HD test result. [11][12][13][14] The decision to proceed with PT may be dynamic and may unfold over time or it may be more automatic or triggered by a particular event. 15 It is shaped by clinical or sociopolitical contexts (e.g., test accessibility and availability, cost, psychiatric diagnoses), as well as other personal and familial factors.…”
Section: Introductionmentioning
confidence: 99%